2010
DOI: 10.1103/physreva.82.032328
|View full text |Cite
|
Sign up to set email alerts
|

Approximating incompatible von Neumann measurements simultaneously

Abstract: We study the problem of performing orthogonal qubit measurements simultaneously. Since these measurements are incompatible, one has to accept additional imprecision. An optimal joint measurement is the one with the least possible imprecision. All earlier considerations of this problem have concerned only joint measurability of observables, while in this work we also take into account conditional state transformations (i.e., instruments). We characterize the optimal joint instrument for two orthogonal von Neuma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This means that if we want to implement a joint measurement of X s and Z t with s, t = 0, the joint measurement process cannot contain a Lüders channel L Zt or L Xs . We remark that it has been earlier shown that a joint measurement process cannot contain both L Zt and L Xs [17]. Our new result hence strengthens that observation.…”
Section: B Phase Damping Channels and Lüder's Channelssupporting
confidence: 90%
“…This means that if we want to implement a joint measurement of X s and Z t with s, t = 0, the joint measurement process cannot contain a Lüders channel L Zt or L Xs . We remark that it has been earlier shown that a joint measurement process cannot contain both L Zt and L Xs [17]. Our new result hence strengthens that observation.…”
Section: B Phase Damping Channels and Lüder's Channelssupporting
confidence: 90%
“…The concept of an instrument gives rise also to another sort of compatibility, as two operations may or may not belong to the range of a single instrument [43]. Further, the limitations on approximate joint measurability of two measurements become different if we our aim is to approximate not only measurement outcome probabilities but also state transformations [36].…”
Section: Incompatibility Of Quantum Observable and Channelmentioning
confidence: 99%
“…However, as already pointed in Ref. [12], this tuple admits more than one joint measurement. The 8-outcome POVMs M (+) , M (−) given by 1, 1), (−1, −1, 1), (−1, 1, −1), (1, −1, −1)} and M ± abc = 0 otherwise are also joint measurements for Φ t * (A (xyz) ), obtained by adding the marginal-preserving perturbation D ± given by D ± abc = ±abcM abc .…”
Section: Examplementioning
confidence: 68%
“…Summary of relations between properties of measurements, tuples of measurements, and joint measurements (in the case where the tuples are jointly measurable). In blue, the previously known results in the literature of quantum measurements [7,12].…”
Section: Examplementioning
confidence: 91%
See 1 more Smart Citation